National-cultural aspect of economical activity of Ukrainian society - Bondarenko, Olga (Actual Problems of Mind, 2017)
The paper is devoted to the analysis of economical mentality the modern Ukrainians and social-economical situation in our society. The author points out the necessity of the formation of the European type economical mentality in the context of Ukrainian reality and discusses the barriers on this way.